THE ROLE OF MUNICIPAL LEGAL AWARENESS AND MUNICIPAL PSYCHOLOGY IN THE PROCESSES OF FORMING THE GLOBALIST POTENTIAL OF THE TERRITORIAL COMMUNITY - Denis O. Bobrovnyk (Alfred Nobel University Journal of Law)
The article is devoted to the scientific and theoretical substantiation of the role of municipal legal awareness and municipal psychology in the processes of forming the globalist potential of the territorial community. In domestic jurisprudence, the topic is investigated for the first time. The author connects the emergence and formation of the globalist potential of the territorial community, firstly, with the formation and development of the system of local self-government in Ukraine as a virtually new political and administrative phenomenon, which actually determined the formation of a system of public power in the post-Soviet state (public state power + public self-government /municipal/ power) and constitutional-legal institution, which led to powerful and systematic municipalization of all aspects of public and state life. The result of such permanent and systemic influence was not only the formation of a system of municipal legal relations in the state and at the level of numerous territorial communities (between their residents-members, between them and local self-government bodies, between them and civil society institutions, between local self-government bodies of various levels , between them and other bodies representing public state power, etc.), but also in fact revolutionary changes in social consciousness (awareness of law) and in social psychology. The author claims that at the first stage of such changes there was a multi-level formation of the municipal consciousness of the population in the form of individual, group and collective forms, which became the objectified result of the constant existence and functioning of a person, his groups and associations in the conditions of local democracy within the boundaries of the territorial community in the philosophical state of everyday life - that is, where a person carries out his life cycle in the process of realizing his existential interests (existential-functional and existential-activity dominants). The second stage is related to the active position of the state regarding further legalization in the form of regulation, norm design (law design) and rule-making (law-making) of various aspects of the formation, development and improvement of the legal status of local self-government, its bodies and subjects (national-legalization dominant), including the fulfillment of the state's international legal obligations in the field of local democracy, which it undertook under the multilateral international treaties signed by it (internationally mandatory dominant). So, at this stage, we are talking about the further development and improvement of municipal legal awareness (normative-psychological dominant) in the context of solving the teleological task of forming municipal psychology (attitudes as social-behavioral guidelines, various habits as typified forms of practical activity) of a person (personality, resident a member of the TG), its groups and associations within the framework of the formation and development of civil society institutions and their further institutionalization into parallel meta- and para-structures of local, regional and national, within the state, social-management, outside the state-legal influence, conglomerate (psycho-activity dominant). Considering the functional purpose of municipal legal consciousness through the disclosure of its functions, the author emphasizes the evolutionary features of the formation of such a form of legal consciousness, which are in the preserved traditions of municipal development and achieved innovations in municipal construction, and also, taking into account their typicality for all human communities, significantly influence the formation their globalist potential.